Conocimiento y sensibilización en la conservación de abejas nativas sin aguijón en estudiantes de secundaria, Parque Nacional Güeppi-Sekime, Loreto 2024 - Pacheco Cardenas, Cybill Patricia (2025)
This study was conducted in the Tres Fronteras Native Community, located within the Güeppí-Sekime National Park (Loreto, Peru). The objective was to characterize the level of knowledge and assess awareness regarding the conservation of native stingless bees among high school students. The research was descriptive-exploratory with a quantitative approach, applied to a purposive sample of 28 students from IE N°60342, selected from a population of 46 enrolled. Data collection was conducted using a 25-item structured survey, with a Cronbach's alpha coefficient of 0.657, considered acceptable for an exploratory study. Statistical analysis included normality tests (Shapiro-Wilk) and Pearson correlation. The results showed that students possessed general knowledge about the cultural and ecological value of stingless bees, although they were limited in management techniques and the transmission of ancestral knowledge. In terms of awareness, a positive assessment of their conservation and recognition of the threats they face were observed. However, the perception of the effectiveness of individual actions was heterogeneous, reflecting the need to strengthen confidence in personal and collective action. Likewise, a willingness to participate in conservation initiatives was identified, although this was limited by a lack of practical experience and technical training. Finally, a low positive correlation was found between knowledge and awareness, suggesting that higher levels of knowledge are associated with greater conservation awareness, although this relationship requires confirmation in studies with larger samples.